The degradable performance of bile‐duct stent based on a continuum damage model: A finite element analysis - Ni, Xiaoyu; Zhang, Yanhong; Pan, Changwang (International journal for numerical methods in biomedical engineering, 2020)
Biomedical magnesium alloy stents have become a hot bed of research focus in interventional therapy for nonvascular diseases. In this study, a numerical model for a balloon‐expandable bile duct stent made of magnesium alloy with laser sculpture is developed to predict the effects of the degradation of the stent on the biomechanical behavior in the stent‐bile duct coupling system. Based on a continuum damage model, the degradable model of the stent is built to understand its performance in an idealized bile duct as it is subject to corrosion over time. The degradation model developed in this study addresses the uniform corrosion and pitting corrosion. By means of the secondary development function of commercial numerical software ANSYS, the finite element analysis procedures were written to control the degradation process based on the technology of element “birth and death,” and it is shown how the three‐dimensional model and approach give the possibility of analyzing for the degradation mechanism of a magnesium alloy stent in the bile duct or other nonvascular cavities. The effects of the degradation of the stent on the bio‐mechanical behavior in the stent‐bile duct coupling system are analyzed by FEM based on a continuum damage model. The degradation model developed in this study addresses the uniform corrosion and pitting corrosion. This research can be used to understand the degradation mechanism of biliary stent.